Assessing footprints of selection in commercial Atlantic salmon populations using microsatellite data. (14th June 2012) - Martinez, V.; Dettleff, P.; Lopez, P.; Fernandez, G.; Jedlicki, A.; Yañez, J. M.; Davidson, W. S.
Summary Relatively large rates of response to traits of economic importance have been observed in different selection experiments in salmon. Several QTL have been mapped in the salmon genome, explaining unprecedented levels of phenotypic variation. Owing to the relatively large selection intensity, individual loci may be indirectly selected, leaving molecular footprints of selection, together with increased inbreeding, as its likely relatives will share the selected loci. We used population differentiation and levels of linkage disequilibrium in chromosomes known to be harbouring QTL for body weight, infectious pancreatic necrosis resistance and infectious salmon anaemia resistance to assess the recent selection history at the genomic level in Atlantic salmon. The results clearly suggest that the marker SSA0343BSFU on chromosome 3 (body weight QTL) showed strong evidence of directional selection. It is intriguing that this marker is physically mapped to a region near the coding sequence of DVL2, making it an ideal candidate gene to explain the rapid evolutionary response of this chromosome to selection for growth in Salmo salar. Weak evidence of diversifying selection was observed in the QTL associated with infectious pancreatic necrosis and infectious salmon anaemia resistance. Overall, this study showed that artificial selection has produced important changes in the Atlantic salmon genome, validating QTL in commercial salmon populations used for production purposes according to the recent selection history.